2017
DOI: 10.1097/phm.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Corticomotor Excitability Effects of Peripheral Nerve Electrical Stimulation to the Paretic Arm in Stroke

Abstract: Advanced ACCREDITATION: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians.The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 0.75 AMA PRA Category 1 Credit(s)™. Physicians should only claim credit commensurate with the extent of their participation in the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…PNS involves stimulating sensory nerves at the sensory threshold level to encourage motor area activation and stimulating a peripheral nerve to activate the corresponding primary sensory area. This is hypothesized to affect the GABA inhibitory system, increase the excitability of the motor cortex, and promote long-term potentiation of the motor area (Kaelin-Lang et al., 2002; Liu & Au-Yeung, 2017; Sawaki, Wu, Kaelin-Lang, & Cohen, 2006; Wu, van Gelderen, Hanakawa, Yaseen, & Cohen, 2005). Therefore, the reason for the effectiveness of PNS in restoring hand function might be that the stimulation of the median and ulnar nerves on the distal forearm encouraged the activation of the portion of the motor area controlling the hand.…”
Section: Discussionmentioning
confidence: 99%
“…PNS involves stimulating sensory nerves at the sensory threshold level to encourage motor area activation and stimulating a peripheral nerve to activate the corresponding primary sensory area. This is hypothesized to affect the GABA inhibitory system, increase the excitability of the motor cortex, and promote long-term potentiation of the motor area (Kaelin-Lang et al., 2002; Liu & Au-Yeung, 2017; Sawaki, Wu, Kaelin-Lang, & Cohen, 2006; Wu, van Gelderen, Hanakawa, Yaseen, & Cohen, 2005). Therefore, the reason for the effectiveness of PNS in restoring hand function might be that the stimulation of the median and ulnar nerves on the distal forearm encouraged the activation of the portion of the motor area controlling the hand.…”
Section: Discussionmentioning
confidence: 99%
“… 59 In addition, peripheral nerve stimulation at ulnar and radial sites for 1 h has been revealed to increase corticomotor function and improve hand dexterity in patients with moderate to severe hemiparesis. 60 Thus, TENS may be utilized as a convenient tool for temporal function and muscle facilitation to maintain therapeutic effects with the provision of proper assistance. Prolonged periods of sensory stimulation, such as TENS combined with activity, can have beneficial effects for treating impaired function after stroke.…”
Section: Neurorehabilitation Therapy Could Potentially Be Taught and mentioning
confidence: 99%
“…The effectiveness of ES for modulation of the excitability of the CST and improvement of dexterity performance of the paretic hand has been reported in patients with mild to moderate paralysis. 21 , 22 Moreover, the additive effect of MI and ES has been reported in healthy adults. Saito and colleagues reported that a combination of MI and peripheral nerve ES enhances the excitability of the CST compared with MI alone or ES alone.…”
Section: Introductionmentioning
confidence: 98%